The Effect of Green Innovation and Ownership Structure on Corporate Financial Performance - Yuyun Isbanah (Manajemen Bisnis, 2021)
The study aimed to determine the effect of green innovation implementation and ownership structure on corporate financial performance. The variables consisted of corporate financial performance, green innovation, managerial ownership, and institutional ownership. The study used a quantitative causality approach. The population of this study is a mining sector company listed on the Indonesia Stock Exchange. The sample was determined with the following criteria: (a) mining sector companies, (b) submit annual reports to IDX in 2020, and (c) not delisting in 2020. The data used was secondary data of the company's annual report and the PROPER awarding data from the Ministry of Environment. Data analysis techniques used multiple Linear Regression with Stata 14.2 software. The results showed that green innovation and managerial ownership did not affect corporate financial performance, while institutional ownership positively affected corporate financial performance. The managerial implication of this research is that in the short term, the presence of institutional investors can improve corporate financial performance.